The study of the hydrogen storage capacity of the Ti atoms coated Si@Ga12 clusters. (14th December 2015) - Tang, Chunmei; Kang, Jing; Zhang, Zhenjun; Zou, Jianfei; He, Xiang; Xu, Yan
Abstract: The generalized gradient approximation based on the density functional theory method is used to investigate the hydrogen storage abilities of the transition metal Ti atoms coated Tim -Si@Ga12 (m = 1, 2) clusters. The average binding energy of the Ti atom to the hollow site on the Si@Ga12 surface and the distance between the neighboring two Ti atoms are 5.20 eV and 2.8 Å, respectively larger than the experimental cohesive energy of bulk Ti (4.85 eV/atom) and the experimental bond length of the Ti2 dimer (1.97 Å), so the clustering of Ti atoms can be prevented, this is critical for large amount hydrogen storage. Ti-Si@Ga12 and Ti2 -Si@Ga12 can adsorb 6 and 12H2 molecules separately with the average adsorption energy of 0.37 eV and 0.30 eV, which would allow hydrogen storage at near-ambient conditions. The Dewar–Kubas interaction mechanism dominates the adsorption of H2 by the Ti-Si@Ga12 and Ti2 -Si@Ga12 structures. The average desorption temperature analysis and the molecular dynamic simulation demonstrate that the structures reported here are favorable for the reversible hydrogen storage at near-ambient conditions. Graphical abstract: The average binding energy of the Ti atoms to the hollow site on the Si@Ga12 surface and the distance between the neighboring two Ti atoms are 5.20 eV and 2.8 Å, respectively larger than the experimental cohesive energy of bulk Ti and the experimental bond length of the Ti2 dimer, so the clustering of Ti atoms can be prevented, this is critical for large amount hydrogen storage. Ti-Si@Ga12 and Ti2 -Si@Ga12 can adsorb 6 and 12H2 molecules separately with the average adsorption energy of 0.37 and 0.30 eV, which is suitable for hydrogen storage under near-ambient conditions. The average desorption temperature analysis and the molecular dynamic simulation explore that the structures reported here are favorable for the reversible hydrogen storage at near-ambient conditions. Highlights: The Ti atoms are strongly binding to the surface of Si@Ga12 and do not suffer from clustering. The stable Ti-Si@Ga12 and Ti2 -Si@Ga12 clusters can store hydrogen with the moderate average adsorption energy. The Tim -Si@Ga12 (m = 1, 2) clusters are favorable for the reversible hydrogen adsorption/desorption at near-ambient conditions.